2020
DOI: 10.3390/molecules25133068
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition, Antioxidant and Anticancer Potentials of Extracts from Rosa banksiae Ait. Flowers

Abstract: Rosa banksiae Ait. (R. banksiae) is a traditional Chinese folk medicine and an ornamental plant. Most previous studies have focused on cultivation and utilization while there are few research papers on the pharmacological activity of R. banksiae. This study aimed to get a better understanding of R. banksiae by extracting polyphenols with fractionated extraction technology. The results showed that ethyl acetate phase (EAP) contained the most polyphenols, while water phase (WP) had the least. HPLC analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In vitro and in vivo investigations have shown few ethnopharmaceutical activities, including antioxidative, anti-inflammatory, and anti-neoplastic effects. 23,25,[51][52][53] Therefore, the present study revealed, for the first time, the beneficial health effects of LUT against DOX-induced oxido-inflammatory responses in the reproductive organs of male Wistar albino rats. Rats exposed to DOX exhibited marked (p < 0.05) diminutions in the mean body weight, thus indicating general toxicity and alterations of metabolic functions.…”
Section: Discussionmentioning
confidence: 85%
“…In vitro and in vivo investigations have shown few ethnopharmaceutical activities, including antioxidative, anti-inflammatory, and anti-neoplastic effects. 23,25,[51][52][53] Therefore, the present study revealed, for the first time, the beneficial health effects of LUT against DOX-induced oxido-inflammatory responses in the reproductive organs of male Wistar albino rats. Rats exposed to DOX exhibited marked (p < 0.05) diminutions in the mean body weight, thus indicating general toxicity and alterations of metabolic functions.…”
Section: Discussionmentioning
confidence: 85%
“…Peroxidation of proteins, lipids, RNA, and DNA affects cellular function, thereby increasing the risk of cardiovascular disease and cancer, and accelerating the process of aging [ 48 ]. Gallic acid is a representative polyphenol that is reported to have alleviating effects on cellular DNA injury resulting from oxidative stress and is known to have many physiological uses owing to its antioxidant, antibacterial, anticancer, and anti-hypertension properties [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…banksiae Ait. (RBW) known as Banksian rose [4] were collected from Merry land Botanical Garden, Cairo, Egypt (30⁰05'37" N31⁰18'51"E), while Rosa polyantha Thunb. ‗Orange fairy' (RPO) and Rosa polyantha Thunb.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The rose is named for Lady Banks, the wife of the botanist Sir Joseph Banks. It is largely cultivated in China especially in Southwest areas [4]. Rosa polyantha Thunb.…”
Section: Introductionmentioning
confidence: 99%